Gendered patterns of migration to Greece - Cavounidis, Jennifer (The Greek Review of Social Research, 2003)
The salience of gender for understanding migration phenomena has come to the forefront over the last decade. Various dimensions of gender relations such as the division of labour between paid and unpaid work, the occupational division of labour, and power relations within the family are integral parts of the structural forces that lead to migration. New data on migration to Greece indicate precisely this importance of gender for understanding migration and the migrant experience. The highly skewed gender composition of various nationalities present in Greece as well as data on the location of the spouses and children of migrants demonstrate that migration patterns are gendered.